The Argumentative Turn in Policy Analysis and Planning - Forester, John, 1948-; Fischer, Frank, 1942- (Book collections on Project MUSE., 1993)
A work from leading planners and policy analysts, representing practical, theoretical and political advances in the field of planning, public administration and public policy.